Treatment of finger degloving injury with acellular dermal matrices: Functional and aesthetic results. Issue 9 (September 2019) - Maruccia, M.; Marannino, P.C.; Elia, R.; Ribatti, D.; Tamma, R.; Nacchiero, E.; Manrique, O.J.; Giudice, G.
Summary: Introduction: Finger degloving injuries (FDIs) represent a challenge in hand surgery. When replantation is not possible, several techniques including loco-regional flaps, pocket abdominal flaps and free flaps have been described as methods to provide skin cover and avoid finger shortening. The aim of this study is to present our experience with acellular dermal matrices (ADMs) in the treatment of FDI. Materials and methods: We retrospectively reviewed the charts of 18 patients who presented with FDI and were treated with ADM between December 2015 and July 2017. Surgical outcomes including complications were analysed, and patient-centred assessments were performed at 12 months of follow-up. Results: The follow-up period ranged from 10 to 20 months. All patients showed good integration and vascularisation of the ADM. All the fingers covered with ADM were firm and soft, with a slim and satisfactory appearance at a mean follow-up of 12 months. No limitations in tendon sliding were observed at dynamic sonography one year after surgery. Conclusion: ADMs could be regarded as a viable option when dealing with FDIs, if replantation is not possible and finger length is to be preserved. On the basis of these results, the surgical treatment of FDI with ADM is a viable option that produces good functional outcomes and cosmetic appearance.